Novel initiator caspase reporters uncover unknown features of caspase-activating cells - Baena-Lopez, L; Arthurton, L; Bischoff, M; Vincent, J; Alexandre, C; McGregor, R (Company of Biologists, 2018)
The caspase-mediated regulation of many cellular processes, including apoptosis, justifies the substantial interest in understanding all of the biological features of these enzymes. To complement functional assays, it is critical to identify caspase-activating cells in live tissues. Our work describes novel initiator caspase-reporters that, for the first time, provide direct information concerning the initial steps of the caspase activation cascade in Drosophila tissues. One of our caspase-sensors has capitalized on the rapid subcellular localization change of a fluorescent marker to uncover novel cellular apoptotic events. These refer to the actin-mediated positioning of the nucleus before cell delamination. The other construct has benefited from a caspase-induced nuclear translocation of a QF transcription factor. This feature enables the genetic manipulation of caspase-activating cells, whilst showing the spatio-temporal patterns of initiator caspase activity. Collectively, our sensors offer experimental opportunities not available by using previous reporters and therefore they have been proven useful to illuminate unknown aspects of caspase-dependent processes in apoptotic and non-apoptotic cellular scenarios.